Analisis Efisiensi Fungsi Intermediasi Bank Pembiayaan Rakyat Syariah (Bprs) Di Provinsi Jawa Tengah Menggunakan Data Evelopment Analysis (DEA) Periode 2014 - Wijanarko, Fajar; , Dr. Didit Purnomo, M.Si; , Nurul Huda, M.Ag (2016)
This research aims to determine and analyze the efficiency of intermediation Islamic Rural Bank (BPRS) in Central Java province using Data Evelopment Analysis (DEA) with input oriented approach in the period of 2014. By using secondary data obtained from the quarterly financial statements 25 BPRS in Central Java province which has been published on the official website of the Otoritas Jasa Keuangan (OJK) is www.ojk.go.id. Based on calculations DEA , in the first quarter there were 16BPRS efficient, in the second quarter there were 17 BPRS efficient, in the third quarter there were 22 BPRS efficient , and in the fourth quarter there were 17 BPRS efficient. During the period of 2014 (Quarter I - Quarter IV), there were 13 BPRS always efficient.